FXR overexpression prevents hepatic steatosis through inhibiting AIM2 inflammasome activation in alcoholic liver disease - Li, Lin; Kong, Lina; Xu, Shuai; Wang, Changyuan; Gu, Jiangning; Luo, Haifeng; Meng, Qiang (Hepatology international, 2024)
Background and purpose Alcoholic liver disease (ALD), a metabolic liver disease caused by excessive alcohol consumption, has attracted increasing attention due to its high prevalence and mortality. Up to date, there is no effective and feasible treatment method for ALD. This study was to investigate whether Farnesoid X receptor (FXR, NR1H4) can alleviate ALD and whether this effect is mediated by inhibiting absent in melanoma 2 (AIM2) inflammasome activation. Methods The difference in FXR expression between normal subjects and ALD patients was analyzed using the Gene Expression Omnibus (GEO) database. Lieber–DeCarli liquid diet with 5% ethanol (v/v) (EtOH) was adopted to establish the mouse ALD model. Liver histopathological changes and the accumulation of lipid droplets were assessed by H&E and Oil Red O staining. Quantitative real-time PCR, Western blotting analysis and immunofluorescence staining were utilized to evaluate the expression levels of related genes and proteins. DCFH–DA staining was adopted to visualize reactive oxidative species (ROS). Results FXR was distinctly downregulated in liver tissues of patients with steatosis compared to normal livers using the GEO database, and in ethanol-induced AML-12 cellular steatosis model. FXR overexpression ameliorated hepatic lipid metabolism disorder and steatosis induced by ethanol by inhibiting the expression of genes involved in lipid synthesis and inducing the expression of genes responsible for lipid metabolism. Besides, FXR overexpression inhibited ethanol-induced AIM2 inflammasome activation and alleviated oxidative stress and ROS production during ethanol-induced hepatic steatosis. However, when FXR was knocked down, the results were completely opposite. Conclusions FXR attenuated lipid metabolism disorders and lipid degeneration in alcohol-caused liver injury and alleviated oxidative stress and inflammation by inhibiting AIM2 inflammasome activation. Graphical abstract